Mengukur Nilai Sosial Program Urban Farming: Studi SROI Pada Buruan SAE di Arcamanik - Cintha Ayunandha Pratama Nugraha; Nanda Ravenska; Putri Wulandari Atur Rejeki; Cintantya Andhita Dara Kirana (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to measure the social, economic, and environmental impacts of the Buruan SAE (Healthy, Natural, Economical) program implemented in Arcamanik District, Bandung City. The Buruan SAE program is designed to improve urban food security by promoting healthy and economical organic-based urban agriculture. This study used a mixed methods approach, combining qualitative and quantitative methods to provide a more comprehensive picture of the program's social impacts. Data were collected through interviews, observations, and documentation conducted with community groups directly involved in the program. This method allowed researchers to explore community perceptions and experiences regarding the benefits they received from the program, as well as the challenges they faced in its implementation. In addition, the economic impact was measured by calculating the Social Return on Investment (SROI) Ratio, which provides an overview of the value of social benefits generated from each unit of investment spent. The results showed that the Buruan SAE program generated an SROI ratio of 3.73:1, meaning that every Rp 1 of social investment spent generated Rp 3.73 in social, economic, and environmental benefits. This demonstrates that the program is not only effective in improving community food security but also has a positive impact on improving the local economy and a healthier environment. Overall, this study concludes that the Buruan SAE program is effective in providing significant benefits, both socially, economically, and environmentally, and can be used as a model for developing sustainable urban food security. Furthermore, the Buruan SAE program also plays a significant role in strengthening social solidarity within the community. Through joint activities in urban agriculture management, the program encourages closer relationships between residents, especially within farmer groups and local communities.